THE KNOWLOEDGE OF THE IMPACT SEXUAL BEHAVIOURS AND ADOLESCENTS DATING BEHAVIORS IN HIGH SCHOOL SURABAYA - Fifi Lailiya; Atika Atika; Nur Ainy Fardana; Rize Budi Amalia (UNIVERSITAS AIRLANGGA, 2020)
AbstractBackground: Knowledge is one of the factors that encourage adolescents to engage in sexual behavior that deviates outside the bond of marriage through the culture of dating adolescent. According to previous research, it was reported that only a small proportion of adolescents had heard about the container or place of obtaining information and consultation regarding reproductive health. This study aims to determine the relationship of knowledge about the impact of premarital sexual behavior with dating behavior in adolescents. Methods: This research method is observational analytic with cross sectional research design. The number of samples was 56 adolescents in high school “X” Surabaya with the sampling technique using stratified random sampling. The independent variable was knowledge about the effects of premarital sexual behavior. The dependent variable was adolescent dating behavior. Results : The results showed that the level of adolescents knowledge on the impact of premarital sex behavior was included in the good category (62,5%) with while dating behavior was in the moderate category (55,4%). Spearman rank test results knowledge with dating behavior in adolescents p = 0.002 (p <0.05). Conclusion : The data showed that there was a relationship of knowledge about the impact of premarital sexual behavior with dating behavior in adolescents.